91.8k views
3 votes
Question is in picture

Question is in picture-example-1
User Malsmith
by
5.7k points

2 Answers

2 votes

Answer:

It is 102.7

Explanation:

Let (h) is the hypotenuse so


h^(2) = {(7x + 4)}^(2) + {(3x)}^(2) \\ x = 13 \\ h^(2) = (95)^(2) + {(39)}^(2) \\ h = √(10546) \\ h = 102.7

I hope that is useful for you :)

User Sashank
by
5.1k points
6 votes

Answer:

hypotenuse = 102.69

Explanation:

7(13) + 4 = 95

3(13) = 39

hypotenuse² = 95² + 39² = 9025 + 1521 = 10546

hypotenuse = √10546 = 102.69

User Quima
by
5.1k points